William Temple Hornaday papers - Hornaday, William T. (William Temple), 1854-1937.
Correspondence, diaries, journals, writings, notebooks, financial records, clippings, scrapbooks, memorabilia, and other papers reflecting Hornaday's career, particularly as director of the New York Zoological Park, 1896-1926. Documents his work with the American Bison Society; Camp Fire Club of America; and Permanent Wild Life Protection Fund. Also documents his activities with the American Defense Society during World War I. Subjects include the Bayne Act, a New York (State) law passed in 1911 for the protection of wild game; natural history; taxidermy; wildlife conservation; protection of wildlife, especially birds and bison; zoological expeditions; French war debt; and Hornaday's real estate ventures in Buffalo, N.Y.
Family correspondents include Hornaday's wife, Josephine Chamberlain Hornaday, and daughter, Helen Ross Hornaday Fielding. Other correspondents include Carl Ethan Akeley, Roy Chapman Andrews, Newton Diehl Baker, Daniel Carter Beard, William Beebe, Charles E. Bessey, Frank Buck, John Burroughs, Andrew Carnegie, Elliot Coues, Raymond Lee Ditmars, Theodore Dreiser, Edith Helen Franz, G. Brown Goode, Madison Grant, Zane Grey, Carl Hagenbeck, W.J. Holland, Charles Evans Hughes, Martin Johnson, S.P. Langley, C. Hart Merriam, Jack Miner, Henry Fairfield Osborn, Maxwell E. Perkins, John M. Phillips, Gifford Pinchot, Franklin D. Roosevelt, Kermit Roosevelt, Theodore Roosevelt, Ernest Thompson Seton, George Shiras, William H. Taft, John Wanamaker, Henry A. Ward, Woodrow Wilson, and the New York Zoological Society.
Library of Congress Prints and Photographs Division.
Conservationist, zoologist, and taxidermist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Akeley, Carl Ethan, -- 1864-1926 -- Correspondence; Andrews, Roy Chapman, -- 1884-1960 -- Correspondence; Baker, Newton Diehl, -- 1871-1937 -- Correspondence; Beard, Daniel Carter, -- 1850-1941 -- Correspondence; Beebe, William, -- 1877-1962 -- Correspondence; Bessey, Charles E. -- 1845-1915 -- Correspondence; Buck, Frank, -- 1884-1950 -- Correspondence; Burroughs, John, -- 1837-1921 -- Correspondence; Carnegie, Andrew, -- 1835-1919 -- Correspondence; Coues, Elliott, -- 1842-1899 -- Correspondence; Ditmars, Raymond Lee, -- 1876-1942 -- Correspondence; Dreiser, Theodore, -- 1871-1945 -- Correspondence; Fielding, Helen Ross Hornaday, -- 1881-1974 -- Correspondence; Franz, Edith Helen -- Correspondence; Goode, G. Brown -- 1851-1896 -- Correspondence; Grant, Madison, -- 1865-1937 -- Correspondence; Grey, Zane, -- 1872-1939 -- Correspondence; Hagenbeck, Carl, -- 1844-1913 -- Correspondence; Holland, W. J. -- 1848-1932 -- Correspondence; Hornaday, Josephine Chamberlain, -- 1854- -- Correspondence; Hughes, Charles Evans, -- 1862-1948 -- Correspondence; Johnson, Martin, -- 1884-1937 -- Correspondence; Langley, S. P. -- 1834-1906 -- Correspondence; Merriam, C. Hart -- 1855-1942 -- Correspondence; Miner, Jack, -- 1865-1944 -- Correspondence; Osborn, Henry Fairfield, -- 1857-1935 -- Correspondence; Perkins, Maxwell E. -- 1884-1947 -- Correspondence; Phillips, John M. -- 1861-1953 -- Correspondence; Pinchot, Gifford, -- 1865-1946 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Roosevelt, Kermit, -- 1889-1943 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Seton, Ernest Thompson, -- 1860-1946 -- Correspondence; Shiras, George, -- 1859-1942 -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; Wanamaker, John, -- 1838-1922 -- Correspondence; Ward, Henry A. -- 1834-1906 -- Correspondence; Wilson, Woodrow, -- 1856-1924 -- Correspondence; New York (State).; American Bison Society; Camp Fire Club of America; New York Zoological Society -- Correspondence; Permanent Wild Life Protection Fund; Birds -- Conservation; Bison -- Conservation; Conservation of natural resources; Conservation of natural resources -- Societies, etc; Debts, Public -- France; Game and game-birds -- Conservation; Natural history; Real property -- New York (State) -- Buffalo; Scientific expeditions; Taxidermy; Wildlife conservation; Wildlife conservation -- Law and legislation -- New York (State); Wildlife conservation -- Societies, etc; World War, 1914-1918.; Zoology; Zoos -- New York (State) -- New York; New York Zoological Park